45. Conferencing Tools and the Productivity Paradox - Nibourg, Theodorus (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2005)
The previous report in this series (Report #44) discusses current attitudes to distance education technology, with specific reference to the counter-productive effects of learning management systems. The current paper pursues this theme in relation to the evolution of online audio-conferencing systems in DE, and revisits the notion of the “productivity paradox” proposed by Solow (1987). It also considers the slow evolution of DE technologies in comparison with the rapid rates of development predicted by Moore’s Law (1965). The paper concludes by outlining the human factors that distance educators must consider in order to harness online audio-conferencing technologies to full advantage.